EXAMINING THE FACTORS THAT AFFECT INTERNSHIP STUDENT TEACHERS' USE OF TECHNOLOGY: A STUDY OF UNIVERSITAS NEGERI MAKASSAR - Aslinda, Aslinda; Arwadi, Fajar (Pedagogy: Jurnal Pendidikan Matematika, 2024)
This study investigates the factors influencing internship student teachers' use of technology at Universitas Negeri Makassar. The research aims to identify key determinants that shape their preferences and attitudes toward integrating technology into teaching practices. Data were collected and analyzed using Confirmatory Factor Analysis (CFA), revealing several critical factors with varying levels of influence based on their loading factors. The strongest predictors of technology use included Student Interest and Motivation (0.81), Perceived Value (0.79), and Self-Efficacy (0.76). These highlight the importance of student engagement, personal confidence, and the perceived utility of technology in driving adoption. Other significant factors were Resources and Infrastructure (0.72), Alignment with Curriculum Goals (0.64), and Administrative Support (0.63), underscoring the role of institutional and logistical support. Moderate contributions were noted from Societal and Cultural Influences (0.61), Government Policies and Mandates (0.57), and Professional Development Opportunities (0.54). These indicate external and professional contexts shaping technology integration. Meanwhile, Innovative Teaching Practices (0.53) and Professional Development (0.43) demonstrated lower impacts, suggesting room for improvement in training initiatives.